Demand and use of health services by Brazilian adolescents, according to the National School Health Survey 2019 - Alanna Gomes da Silva; Crizian Saar Gomes; Alan Cristian Marinho Ferreira; Deborah Carvalho Malta (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze the demand and use of health services by Brazilian adolescents, according to sociodemographic characteristics. Methods: Cross-sectional study with data from the 2019 National School Health Survey, that assessed 124,898 adolescents aged 13 to 17 years. The crude and adjusted prevalence ratios (RPaj) by sex, age, and school administrative status and their 95% confidence intervals (95%CI) were calculated for the variables "search for a service or health professional", "search for a Basic Health Unit" and "assistance at the Basic Health Unit", using Poisson regression with robust variance. Results: The demand for a health service was reported by 56.56% (95%CI 55.82-57.29) of the adolescents and was lower among male students (RPaj: 0.95; 95%CI 0.94-0.95); those with black skin color (RPaj: 0.95; 95%CI 0.94-0.97), brown skin color (RPaj: 0.97; 95%CI 0.96-0.98), yellow skin color and indigenous ethnicity (RPaj: 0.95; 95%CI 0.94-0.97); public school students (RPaj: 0.90; 95%CI 0.89-0.90); and rural residents (RPaj: 0.96; 95%CI 0.94-0.98). A Basic Health Unit was the service sought by 74.08% (95%CI 73.21-74.94) of adolescents, more frequently among students of brown skin color (RPaj: 1.06; 95%CI 1.03-1.08), from public schools (RPaj: 1.32; 95%CI 1.29-1.35) and residing in rural areas (RPaj: 1.05; 95%CI 1,01-1,09). The main reason for seeking the Basic Health Unit was vaccination (27,93%; 95%CI 27,07-28,81). Conclusion: More than half of the adolescents searched for a health service, which means that this group has a high demand. However, health inequalities still persist and point to the importance of health care planning, reception conditions, and the quality of care provided.